Low temperature mixed spin state of Co3+ in LaCoO3 evidenced from Jahn-Teller lattice distortions - Gnezdilov, V.; Choi, K.-Y.; Pashkevich, Yu.; Lemmens, P.; Shiryaev, S.; Bychkov, G.; Barilo, S.; Fomin, V.; Yeremenko, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
One- and multi-phonon excitations of the single crystalline LaCoO3 were studied using Raman spectroscopy in the temperature region of 5–300 K. First-order Raman spectra show a largernumber of phonon modes than allowed for the rhombohedral structure. Additional phonon modesare interpreted in terms of activated modes due to lattice distortions, arising from the Jahn–Teller (JT) activity of the intermediate-spin (IS) state of Co3+ ions. In particular, the 608-cm–1 stretching-type mode shows anomalous behavior in peak energy and scattering intensity as afunction of temperature. The anomalous temperature dependence of the second-order phonon excitations spectra is in accordance with the Franck–Condon mechanism that is characteristic for a JT orbital order.